Operational effects of plyometric training in the development of explosive strength of mountain run athletes - Bakaev, V. V.; Poniasov, O. E.; Vasilyeva, E. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of training mountain running athletes to overcome steep climbs using plyometric training.